(untitled) (Journal of Asian Development Studies, 2023)
Stress strains the mind, emotions and motivates the person to face difficult circumstances head-on. On the other hand, excessive stress has negative short and long-term repercussions on one’s mental and physical well-being. The purpose of the current study was to ascertain how everyday stress is among teenagers in Pakistan and what effect it has on their mental and physical health. As a theoretical framework, the Thomas Theorem was used. The study’s sample size consisted of sixteen pupils from the 13–16 age group in Rawalpindi Province, Punjab. To investigate the issue, in-depth interviews were conducted with students in the ninth and tenth grades using an interview guide. The field data was interpreted using thematic analysis. The literature study and field data revealed that the primary sources of stress were parental expectations, relationships between siblings, and beauty stress. The results showed that these stressors have specific psychological and physical side effects, including headaches, irritability, low motivation, and a propensity for making poor decisions. Stress appears to have an impact on a teen’s health in addition to their academic achievement.